Selection of Rhizobium spp. strains in culture medium for acid soils - Silva, Gisele Gomes da; Franco, Avilio A. (Pesquisa Agropecuaria Brasileira, 2014)
A group of Rhizobium sp. strains isolated from several legume trees from diverse environments was assayed in culture medium at pH 4,6 with and without 50 µM Al3+, using bromocresol green indicator and at pH 6,2 using bromocresol purple indicator. From 211 Rhizobium strains isolated from legume trees, 85.7%, 48.8% and 28.0% from the subfamilies Caesalpinioideae, Mimosoideae and Papilinioideae respectively did grow in culture medium with pH 4.6 and without 50 µM Al3+.One strain did grow without but not with AI3+. Of the 211 strains 77 grow alter increasing the pH of the medium and only 19 were able to grow at pH 4,6 without increasing the pH of the medium. These strains seem the most promising for further tests with plants for acid soils.
Keywords: legume tree; symbiosis